Sulfate Transporters in Dissimilatory Sulfate Reducing Microorganisms: A Comparative Genomics Analysis - Marietou, Angeliki; Røy, Hans; Jørgensen, Bo B.; Kjeldsen, Kasper U. (Frontiers in Microbiology, 2018)
The first step in the sulfate reduction pathway is the transport of sulfate across the cell membrane. This uptake has a major effect on sulfate reduction rates. Much of the information available on sulfate transport was obtained by studies on assimilatory sulfate reduction, where sulfate transporters were identified among several types of protein families. Despite our growing knowledge on the physiology of dissimilatory sulfate-reducing microorganisms (SRM) there are no studies identifying the proteins involved in sulfate uptake in members of this ecologically important group of anaerobes. We surveyed the complete genomes of 44 sulfate-reducing bacteria and archaea across six phyla and identified putative sulfate transporter encoding genes from four protein families based on homology. We did not find evidence that ABC-type transporters (SulT) are involved in the uptake of sulfate in SRMs. We speculate that members of the CysP sulfate transporters could play a key role in the uptake of sulfate in thermophilic SRMs. Putative CysZ-type sulfate transporters were present in all genomes examined suggesting that this overlooked group of sulfate transporters might play a role in sulfate transport in dissimilatory sulfate reducers. Our in silico analysis highlights several targets for further molecular studies in order to understand this key step in the metabolism of SRMs.